Implementing district level integrated water management with stakeholder participation - El-Sharkawy, Moamen, author; El-Diasty, Amira, author; Barakat, Essam, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
Increasingly it is understood that water management is best served by an integrated package of services and practices delivered at the local level. The Egyptian Ministry of Water Resources and Irrigation (MWRI) is decentralizing its internal functions and devolving its authority to the local level. Consolidation of MWRI district offices and integration of water management functions at this level supports the decentralized management goal. Forming Branch Canal Water Users' Associations (BCWUA) promotes stakeholders' participation. Historically, teams from the MWRI headquarters established water users' associations in Egypt. A change initiated under this project was to build the participatory management skills of the Integrated Water Management Districts (IWMD) and to delegate to them the responsibility for implementing the program establishing BCWUAs in their district. This approach enhances the potential for sustainability because of the close working relations built between farmers and IWMD staff; project districts are seeing a significant reduction in the number of formal complaints from farmers. Memoranda of understanding defining the roles and responsibilities of the respective signatories are signed by the MWRI and the established BCWUAs. This approach has been used to establish 94 BCWUAs, covering all branch canals within the command areas of four IWMDs, about 145,000 acres.
Integrated water management
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."